Implementasi Pendekatan Ketrampilan Proses dengan Metode Inkuiri Melalui Kolaborasi Guru dan Dosen (Team Teaching) untuk meningkatkan Hasil Belajar - R. Bekti Kiswardianta (Jurnal Pendidikan, 2009)
The main objectives of this research is to develop the achievement of the students of grade IX A of SMP 1 Takeran, Magetan through the implementation of process skill approach under inquiry method through collaboration of teachers and lecturers. The research setting includes grade IX A s SMP 1 Takeran, Magetan, the subject of the research are all students of this class which covers 33 people, including 16 males and 17 females. Data are drawn from students’ achievement through test, students’ motivation through close questionaire, students’ process skill through obsrvation checklist, and students’ activity through actvivity record. The analysis brings abouyt results, that: 1) in the cognitive domain, the student achievement raises from 56.90 to 64.10 in cycle I, and it becomes 71.20 in cycle II. 2) the percentage of threshold level raises from 12% to 42% in cycle I, and it becomes 87% in cycle II. 3) in the affective domain, the student motivation raises from 30% of those with high motivation scale in cycle I to 88% in cycle II; students’ process skill raises from 42% of those with high scale skill in cycle I to 91% in cycle II. The results are then concluded that the implementation of process skill under inquiry model through collaboration of teachers and lecturers for the students of grade IX A SMP 1 Takeran, Magetan can improve the students’ learning outcomes.